Characterization of Efficacy and Flavonoid Levels in Sorghum Extracts of Suri 4 Variety with Different Levels of Drought Stress - Susilo, Edi; Setyowati, Nanik; Pujiwati, Hesti (International Journal of Integrative Sciences, 2025)
Bioherbicides that utilize the allelopathic properties of sorghum plants that experience drought stress are fundamental to sustainable agriculture. This study aimed to look at the efficacy characteristics and flavonoid levels of Suri 4 extracts that have experienced various levels of drought stress. Extract materials were prepared from May to July 2024 at Bengkulu University Greenhouse, Kandang Limun, Bengkulu City, and bioassay tests were conducted in August 2024. Flavonoid analysis was performed at the Integrated Research and Testing Laboratory (LPPT) of Gadjah Mada University in August 2024. This research used a completely randomized design with one factor. One sorghum variety, Suri 4, was planted with water stress treatment through watering patterns every day, every 2 days, every 3 days, every 4 days, and every 5. The bioassay experimental unit was a petri dish, and the experiment was repeated four times. Each petri dish was given 10 mL of water extract, and 25 mung bean seeds were planted and incubated for three days. The results showed that the highest flavonoid levels were achieved by the 5-day watering pattern (3841.65 µg/g), and the lowest flavonoid levels were completed by the daily watering pattern (2948.07 µg/g). The highest germination inhibition was due to the sorghum water extract from the 4-day and 5-day watering patterns and was the best bioherbicide pioneer